A Method for Identification of Cryptosporidium parvum from River Water Using Low-Vacuum SEM - MURATA, Iwao; MOROZUMI, Satoshi; MURATA, Rie; SUZUKI, Takeo; SUZUKI, Jun (Japanese Journal of Food Microbiology, 1998)
In June 1996, the outbreak of waterborne cryptosporidiosis in Saitama prefecture, Japan caused prolonged diarrheal illness in more than 8, 000 people who drank tap water contaminated with Cryptosporidium parvum oocysts. The Ministry of Health and Welfare had to introduce a provisional determination method of Cryptosporidium consisting of an immunofluorescence assay and Nomarski differential interference contrast microscopy. For river water samples, however, this method cannot distinguish C. parvum from other C. parvum-like organisms such as free-living protozoan because of non-specific fluorescence and structural resemblance to C. parvum oocysts. In this study, the microstructure of C. parvum oocysts of a sample was directly observed using a low-vacuum scanning electron microscope (SEM). The sample used for observation river water to which concentrated C. parvum oocysts were previously added . The sample was filtered on a specimen stub, washed with distilled water, then frozen with liquid nitrogen. As a result of this method, C. parvum oocysts could be observed at a>2, 000×magnification and the fine microstructure such as oocyst-wall and four sporozoites could be seen at 10, 000×magnification. Therefore, these results were concluded that the low-vacuum SEM method is useful for discrimination and identification of C. parvum oocysts.